Efficacy and safety of Danlou tablets in the treatment of stable angina pectoris with intermingled phlegm and blood stasis syndrome in coronary heart disease: a multicenter randomized controlled study - Li, Zeng; Li, Han; Li, Zheng; Zhou, Yushi; Yang, Wei; Ao, Yuhan; Xiang, Xinghua; Li, Chongchai; Zhang, Mingxue (Frontiers in Cardiovascular Medicine, 2024)
Objectives: In this study, we assessed the clinical efficacy and safety of Danlou tablets in the treatment of stable angina pectoris (SAP) with intermingled phlegm and blood stasis(IPBS), to provide high-quality evidence-based medical evidence for the prevention and treatment of Coronary Heart Disease. Methods: In the multicenter, practical randomized controlled study, 304 patients diagnosed with stable angina pectoris with IPBS enrolled from 12 national traditional Chinese medicine (TCM) clinical research centers in China, were randomly assigned to the treatment group and the control group at a ratio of 1:1. Each group was divided into four subgroups based on the results of TCM syndrome differentiation: IPBS, IPBS combined with qi deficiency(IPBS-QD), IPBS combined with qi stagnation(IPBS-QS), and IPBS combined with toxin accumulation(IPBS-TA). The control group was treated with routine Western medicine. Based on routine Western medicine treatment, the treatment group was treated with Danlou tablets (IPBS) or